Resilience-by-Design: Extracting Resilience Requirements Using the Resilience Graph in the Automotive Concept Phase - Mpidi Bita, Isaac; Ugur, Elif; Hovemann, Aschot; Dumitrescu, Roman (Future Internet)
The complexity and interconnectivity of modern automotive systems are rapidly increasing, particularly with the rise of distributed and cooperative driving functions. These developments increase exposure to a range of disruptions, from technical failures to cyberattacks, and demand a shift towards resilience-by-design. This study addresses the early integration of resilience into the automotive design process by proposing a structured method for identifying gaps and eliciting resilience requirements. Building upon the concept of resilience scenarios, the approach extends traditional hazard and threat analyses as defined in ISO 26262, ISO 21448 and ISO/SAE 21434. Using a structured, graph-based modeling method, these scenarios enable the anticipation of functional degradation and its impact on driving scenarios. The methodology helps developers to specify resilience requirements at an early stage, enabling the integration of resilience properties throughout the system lifecycle. Its practical applicability is demonstrated through an example in the field of automotive cybersecurity. This study advances the field of resilience engineering by providing a concrete approach for operationalizing resilience within automotive systems engineering.

Theoretical Foundations of the Web: Cognition, Communication, and Co-Operation. Towards an Understanding of Web 1.0, 2.0, 3.0 - Fuchs, Christian; Hofkirchner, Wolfgang; Schafranek, Matthias; Raffl, Celina; Sandoval, Marisol; Bichler, Robert (Future Internet)
Currently, there is much talk of Web 2.0 and Social Software. A common understanding of these notions is not yet in existence. The question of what makes Social Software social has thus far also remained unacknowledged. In this paper we provide a theoretical understanding of these notions by outlining a model of the Web as a techno-social system that enhances human cognition towards communication and co-operation. According to this understanding, we identify three qualities of the Web, namely Web 1.0 as a Web of cognition, Web 2.0 as a Web of human communication, and Web 3.0 as a Web of co-operation. We use the terms Web 1.0, Web 2.0, Web 3.0 not in a technical sense, but for describing and characterizing the social dynamics and information processes that are part of the Internet.